2003
DOI: 10.1002/ffj.1180
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the essential oil of Pallenis spinosa (L.) Cass. (Asteraceae)

Abstract: The essential oil of Pallenis spinosa (L.) Cass. was obtained by hydrodistillation. In total 38 components were identified by GC and GC-MS. Oxygenated sesquiterpenoids amounted to 60.2% of the oil. The main components were germacra-1(10),5-dien-3,4-diol (18.4%), α-cadinol (14.1%), 3-acetoxygermacra-1(10),5-dien-4-ol (13.0%), T-cadinol (8.2%) and δ-cadinene (5.8%). The oil does not show antimicrobial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Several earlier studies have focused on the metabolic products of P. spinosa for taxonomic and potential medicinal applications. It has been reported that the plant is rich in sesquiterpenes and oxygenated sesquiterpenoids . Chemical analysis of the volatile oil extracted from fresh flower heads of the plant identified high percentages of oxygenated sesquiterpenoids, such as germacra‐1(10),5‐diene‐3,4‐diol, α ‐cadinol, 3‐acetoxygermacra‐1(10),5‐dien‐4‐ol, T‐cadinol, and δ ‐cadinene .…”
Section: Introductionmentioning
confidence: 99%
“…Several earlier studies have focused on the metabolic products of P. spinosa for taxonomic and potential medicinal applications. It has been reported that the plant is rich in sesquiterpenes and oxygenated sesquiterpenoids . Chemical analysis of the volatile oil extracted from fresh flower heads of the plant identified high percentages of oxygenated sesquiterpenoids, such as germacra‐1(10),5‐diene‐3,4‐diol, α ‐cadinol, 3‐acetoxygermacra‐1(10),5‐dien‐4‐ol, T‐cadinol, and δ ‐cadinene .…”
Section: Introductionmentioning
confidence: 99%
“…While P. spinosa showed the lowest yield (0.04%) [13], the other species of the genus studied till date had similar results: A. graveolens showed an yield (0.06%) [12] and A. maritimus from Italy showed the yield of 0.06% [17]. It is worth noting that for P. spinosa and A. maritimus, the yields were calculated on fresh weight.…”
Section: Resultsmentioning
confidence: 92%
“…Although Asteriscus is not a very large genus, few studies have been published related to it [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The study of the molecular systematic of some Macaronesian species exposed that Asteriscus is paraphyletic [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations